De-familiarizing readings : essays from the Austin Joyce Conference - Friedman, Alan Warren; Rossman, Charles (European Joyce studies, 2009)
Unlike many recent Joyce studies, De-familiarizing Readings eschews the theoretical and ideological and instead plants itself on firmer ground. Its seven outstanding Joyce scholars share a love of the "stuff" of texts, contexts, and intertexts: data and.